Patients with atrial fibrillation in outpatient practice: clinical characteristics and outcomes over a 10-year observation period (data from the REQUAZA AF registrу - Yaroslavl) - V. V. Yakusevich; V. Vl. Yakusevich; S. Yu. Martsevich; M. M. Lukyanov; O. M. Drapkina (Столичная издательская компания, 2023)
Aim. To present clinical characteristics and assess serious adverse outcomes (death, acute cardiovascular events) in outpatients with atrial fibrillation (AF) in one of the Yaroslavl clinics for 10 years.Material and methods. A total of 212 patients with AF aged from 23 to 94 years were included in the REQUAZA AF registrу - Yaroslavl at the first visit to the clinic in 2013. Their health status was monitored over 10,5 years through in-person visits, phone contacts with patients, their relatives, and treating physicians. Recorded data included the AF type, comorbid conditions, extent and quality of examinations and treatments, development of serious adverse events, and mortality. Statistical processing was carried out using the Microsoft Office 365 application software package.Results. Most patients (66,5%) were diagnosed with persistent AF. Paroxysmal, persistent, and newly detected forms were observed in 26,4%, 3,8%, and 3,3% of patients, respectively. Most AF patients had concomitant cardiovascular diseases, most frequently hypertension (96,7%), heart failure (91,6%), and coronary artery disease (91,2%). A total of 54 patients (25,5%) had prior stroke or transient ischemic attack. Complete information was obtained for 203 patients (95,8%), of which 164 (78,5%) passed away during the follow-up period. The leading death cause was cardiovascular disease, particularly cerebrovascular events (n=111; 67,7%). The highest mortality was recorded within the first two years of follow-up, during which more than a quarter (25,1%) of the registered patients had died. The COVID-19 pandemic did not significantly affect the mortality rates. The most common AF complications were stroke and transient ischemic attack, with a total of 74 episodes in the history and follow-up period, including 7 recurrences.Conclusion. Ambulatory AF patients represent a group with a high frequency of cardiovascular events and fatal outcomes. In the observed group of ambulatory AF patients, annual mortality exceeded 10%, and over 3/4 of patients died within 10 years. The leading death cause was cardiovascular disease, primarily cerebrovascular events.